KADAR ALKOHOL, KADAR LEMAK, TOTAL PADATAN TERLARUT, DAN TOTAL MIKROBA KEFIR SUSU KERBAU DENGAN KONSENTRASI STARTER YANG BERBEDA - Surya, Karina Rizqy Anggita; Rizqiati, Heni; Nurwantoro, Nurwantoro (Program Studi Teknologi Pangan, 2024)
Penelitian ini bertujuan untuk mengetahui pengaruh konsentrasi kefir grain terhadap kadar alkohol, kadar lemak, total padatan terlarut dan total mikroba kefir susu kerbau dan untuk mengetahui apakah parameter tersebut sesuai dengan standar yang telah ditentukan. Penelitian menggunakan Rancangan Acak Lengkap (RAL) dengan perlakuan yang diberikan adalah (T1) konsentrasi kefir grain 2,5%, (T2) konsentrasi kefir grain 5%, (T3) konsentrasi kefir grain 7,5%, dan (T4) konsentrasi kefir grain 10%. Parameter yang diamati adalah kadar alkohol, kadar lemak, total padatan terlarut dan total mikroba. Data hasil pengujian dianalisis menggunakan uji Analysis of Variance (ANOVA) dengan taraf signifikansi 5% dan apabila terdapat perbedaan maka dilanjutkan dengan uji Duncan. Konsentrasi kefir grain memberikan pengaruh nyata (p<0,05) terhadap kadar lemak, kadar alkohol, total padatan terlarut dan total mikroba. Semakin banyak konsentrasi kefir grain maka kadar alkohol dan total mikroba semakin meningkat. Semakin banyak konsentrasi kefir grain maka kadar lemak dan total padatan terlarut semakin menurun.The research aims to determine the effect of kefir grain concentration on alcohol content, fat content, total dissolved solids and total buffalo milk kefir microbes and to find out whether these parameters are in accordance with predetermined standards.The study used a Completely Randomized Design (CRD) with treatments given were (T1) kefir grain concentration of 2.5%, (T2) 5% kefir grain concentration, (T3) kefir grain concentration of 7.5%, and (T4) concentration 10% kefir grain. The parameters observed were alcohol content, fat content, total dissolved solids and total microbes. Data from the test results were analyzed using the Analysis of Variance (ANOVA) test with a significance level of 5% and if there is a difference then proceed with the Duncan test. Kefir grain concentration has a significant effect (p<0,05) on fat content, alcohol content, total dissolved solids and total microbes. The more concentrations of kefir grain, the alcohol content and total microbes increase. The more concentration of kefir grain, the fat content and total dissolved solids decreasesThe research aims to determine the effect of kefir grain concentration on alcohol content, fat content, total dissolved solids and total buffalo milk kefir microbes and to find out whether these parameters are in accordance with predetermined standards.The study used a Completely Randomized Design (CRD) with treatments given were (T1) kefir grain concentration of 2.5%, (T2) 5% kefir grain concentration, (T3) kefir grain concentration of 7.5%, and (T4) concentration 10% kefir grain. The parameters observed were alcohol content, fat content, total dissolved solids and total microbes. Data from the test results were analyzed using the Analysis of Variance (ANOVA) test with a significance level of 5% and if there is a difference then proceed with the Duncan test. Kefir grain concentration has a significant effect (p<0,05) on fat content, alcohol content, total dissolved solids and total microbes. The more concentrations of kefir grain, the alcohol content and total microbes increase. The more concentration of kefir grain, the fat content and total dissolved solids decreases.